The Comparative Parliamentary Democracy Data Archive - Wolfgang Müller; Torbjörn Bergman; Kaare Strøm (Swedish National Data Service, 2011)
Datasetet i "The Comparative Parliamentary Democracy Data Archive" består av data på regeringsnivå för 17 västeuropeiska demokratier från 1945 till och med 1 januari 1999. Totalt ingår 424 olika koalitions-, enpartis- och partiobundna regeringar. Data från Grekland, Portugal och Spanien finns enbart från tiden efter demokratiseringen av dessa länderna under 1970-talet, medan data från Frankrike är begränsad till den femte republiken med start 1959. För detta dataset kan man säga att världen "frös" den 1 januari 1999. De sista observationerna för varje land är kodad på grundval av den information som fanns tillgänglig detta datum. Syfte: Syftet med projektet är att studera västeuropeisk politik utifrån ett "principal-agent"-perspektiv. The Comparative Parliamentary Democracy Data Archive data set consist of cabinet-level data of 17 Western European democracies for post-WWII cabinets through January 1, 1999. All together, a total of 424 coalitions, single party and non-partisan cabinets are included. Data for Greece, Portugal and Spain exist only after their democratizations in the 1970s, while data on France is limited to the Fifth Republic beginning in 1959. For the purposes of our data set, it can be said that the world "froze" on January 1, 1999. The last observation in each country is coded on the basis on the information that was available on that day. Purpose: The Comparative Parliamentary Democracy project examines West European parliamentary politics from a principal–agent perspective.